Famagusta maritima
1 online resource.
Keywords: Famagusta Maritima: Mariners, Merchants, Pilgrims and Mercenaries presents a collection of scholarly studies spanning the thousand year history of the port of Famagusta in Cyprus. This historic harbour city was at the heart of the Crusading Lusignan dynasty, a possession of both Genoa and Venice during the Renaissance, a port of the Ottoman Empire for three centuries, and in time, a strategic naval and intelligence node for the British Empire. It is a maritime space made famous by the realities of its extraordinary importance and influence, followed by its calamitous demise. Contributors are: Michele Bacci, Lucie Bonato, Tomasz Borowski, Mike Carr, Pierre-Vincent Claverie, Dragos Cosmescu, Nicholas Coureas, Marko Kiessel, Antonio Musarra, William Spates, Asu Tozan, Ahmet Usta, and Michael Walsh.